Effects of different fertilizing models on growth of single crop rice and nitrogen and phosphorus runoff losses - WANG Xinxia; WANG Jifeng; HOU Qiong; WANG Xiaojun; NI Wuzhong (浙江大学学报. 农业与生命科学版, 2020)
A field experiment with four typical fertilization models such as conventional fertilization (CF), conventional recommended fertilization (CRF), optimized soil testing for formulated fertilization (TF) and application of organic manure as a partial replacement for chemical fertilizers based on optimized soil testing for formulated fertilization (TFM) was conducted. The responses of single crop rice yield and runoff losses of nitrogen and phosphorus from paddy fields to different fertilization models were investigated. The results showed that the grain yield of the three improved fertilization models increased by 2.80%-3.63% compared with the conventional fertilization, and nitrogen and phosphorus contents in various parts of rice plants kept at the similar levels. The cumulative total nitrogen runoff losses of CRF, TF and TFM treatments decreased by 2.75%, 14.15% and 33.28%, respectively, and the cumulative total phosphorus runoff losses decreased by 19.02%, 21.31% and 29.51%, respectively. In general, three improved fertilization models can meet nitrogen and phosphorus needs of rice plants, increase grain yield, and control the runoff losses of nitrogen and phosphorus effectively, among which TFM is the best.